Uji Klinik Keamanan Ramuan Jamu Penurun Kolesterol - Zulkarnain, Zuraida; Triyono, Agus; Ardiyanto, Danang; Saryanto, Saryanto (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Research on the safety of Jamu (herbal medicine) formula is important to guarantee its use in community. The Jamu Saintification development program has been resulted a cholesterol-lowering herb containing of 7 plants. This study aimed to determine the safety of the cholesterol-lowering herb. This study is a phase one of clinical trial with a pre-post group design, a single arm, involving 50 subjects with mild hypercholesterolemia without any complications and comorbidities. The intervention was conducted for 28 days at the Hortus Medicus Herbal Medicine Research House (RRJ) in 2014. Outcome parameters included clinical signs and symptoms, liver function laboratory tests (SGOT, SGPT), renal function (ureum, creatinine) and routine blood counts (hemoglobin, leukocyte, platelets, hematocrit). Subjects were requested to boil the herb everyday and drank it twice a day. The data were analyzed descriptively and statistically using SPSS. The results showed increasing in bowel frequencies of 92% subjects and abdominal pain in bowel movements of 34% subjects. These effects were still in a normal range and can be tolerated by the subjects. The paired t test analysis showed no differences in average laboratory parameters on day (D)-14 and D-28 compared to the baseline (p > 0.05). The cholesterol-lowering herbal medicine does not change the function of the liver, kidneys and blood, with mild side effects of increasing the frequencies of bowel movements and stomachaches.